Metal-coated fibre Bragg grating sensor for electric current metering - Cavaleiro, P.M. (2019)
A hybrid fibre optic current sensor combining a metal-coated fibre Bragg grating with a standard current transformer is described. Measurements of the RMS current of power lines at 50 Hz with a resolution of 2 mA is demonstrated.